Controllable surface carrier type of metal oxide nanocrystals for multifunctional photocatalysis - Han Li; Yingchun Ding; Kaiyi Luo; Qiuping Zhang; Huan Yuan; Shuyan Xu; Ming Xu (iScience)
Summary: Selectively harnessing photo-induced carriers to control surface photo-redox reactions can enable currently limited specificity in photocatalytic applications. By using a new approach to switching between dominant electron and hole charge transfer on the surfaces of metal oxide nanocrystals, depending on the optimal carrier for specific application functionality in photocatalytic pollutant degradation, H2 production, CO2 reduction, and gas sensing. The approach is based on the surface redox properties of custom-designed p-n hetero-structured hybrid nanoparticles (NPs) containing copper oxide, and wide-gap metal oxide semiconductors (MOSs). The customized CuxO/ZnO (CXZ) heterostructures ensure effective charge separation and surface reactions driven by UV-vis excited highly reactive holes and show high performance in the photo-oxidative degradation of organic dyes and NO2 gas sensing. By switching the dominant surface carrier type from holes to electrons, the hybrids exhibit excellent performance in photocatalytic H2 evolution and CO2 reduction. This work offers a generic approach to engineering multipurpose photocatalytic materials.